Relating the biogeochemistries of zinc, cobalt, and phosphorus to phytoplankton activities in the sea - Wisniewski, Rachel J. (Rachel Jane), 1978- (Massachusetts Institute of Technology, 2006)
Thesis (Ph. D.)--Joint Program in Chemical Oceanography (Massachusetts Institute of Technology, Dept. of Earth, Atmospheric, and Planetary Sciences; and the Woods Hole Oceanographic Institution), 2006. Includes bibliographical references. This thesis explores the potential of zinc, cobalt, and phosphorus to influence primary production in the subarctic North Pacific, the Bering Sea, and the North Atlantic Ocean. In the North Pacific and Bering Sea, total zinc concentrations were measured along a near-surface transect and in selected deep profiles. Zinc speciation was also measured with a novel anodic stripping voltammetry method, and the results were consistent with previous studies using different methods. The potential for zinc to impact primary production in the North Pacific was demonstrated in a shipboard incubation and by comparing two phytoplankton pigment markers to total zinc and free zinc ion concentrations. In the North Atlantic, total dissolved zinc and cobalt concentrations were measured and compared to concentrations of dissolved inorganic phosphorus and chlorophyll. In some areas of the North Atlantic the concentrations of zinc and cobalt were decoupled.The relationship between cobalt and inorganic phosphorus suggests that cobalt drawdown may be related to a high alkaline phosphatase related demand at low phosphorus concentrations. This trend compliments a shipboard incubation where alkaline phosphatase activities increased after cobalt addition. The presence of measurable alkaline phosphatase activity indicated that the phytoplankton community in the Sargasso Sea was experiencing phosphorus stress. Shipboard incubations generally confirmed this with inorganic phosphorus additions resulting in chlorophyll increases at 4 out of 5 stations. Further, the addition of dissolved organic phosphorus, as either a phosphate monoester or a phosphonate compound, resulted in a chlorophyll increase in 3 out of 3 incubations. This suggests that dissolved organic phosphorus may be an important phosphorus ...